Grounded Impedance Simulator Topologies Employing Minimum Passive Elements - Faseehuddin, Mohammad; Sampe, Jahariah; Hamid Md Ali, Sawal (International Journal of Engineering and Technology, 2018)
In this research three new grounded inductance simulators (GIS) are proposed. In addition, frequency dependent negative resistor (FDNR) and grounded capacitor (GC) simulators are also developed. The voltage differencing current conveyor (VDCC) is utilized in the design. All the developed simulator circuits need a single active block and only two grounded passive components. All the designed simulator circuits are perfectly tunable and did not suffer from passive component matching constraints. To demonstrate the performance of the inductor, FDNR and GC circuits they are employed in designingÂ  current mode parallel RLC multifunction filter, low pass third order Butterworth filter and RLC resonance circuits. The VDCC is designed in 0.18Î¼m CMOS technology parameters from TSMC and simulated in P-Spice software to prove the theoretical predictions.Â